Focus Group Discussion (FGD) dan Penyuluhan Pengolahan Produk Lokal Berbasis Ikan untuk Pencegahan Stunting di Sekolah Alam Sahabat Qur’an Kabupaten Siak - Rahmayuni Rahmayuni; Rosnita Rosnita; Roza Yulida; Yulia Andriani; Yanti Nopiani; Febriana Sabrian; Evy Rossi; Annisa Nazifa Salman (Unri Conference Series: Community Engagement, 2025)
This community service activity began with the implementation of a Focus Group Discussion (FGD) with partners, which served as an initial exploration to design service programs that were relevant to the needs of the community. Partners in this activity are the manager of the school business unit and the parents of students. The results of the FGD resulted in an agreement on the focus of activities with stages, namely: (1) Education to improve food quality and nutrition in the prevention of stunting from an early age, and (2) Processing of local fish products (snakehead fish) as a zero waste-based food diversification. Through this FGD, an overview of needs, challenges, and opportunities that can be the basis for the implementation of counseling programs is obtained. It is hoped that the results of this activity can increase partners' knowledge about the processing of local fish food products in an effort to prevent stunting.